2017
DOI: 10.1080/21645515.2017.1303582
|View full text |Cite
|
Sign up to set email alerts
|

Immune infiltration of tumor microenvironment following immunotherapy for glioblastoma multiforme

Abstract: Autologous dentritic cell immunotherapy has been proven effective in treating tumors outside the central nervous system. Current evidence from phase I and II trials suggest a similar efficacy for central nervous system tumors as well and that an active immune response against these tumors can be generated. We aim to review the literature to identify the types of immune responses against gliomas found to be generated by dendritic cell vaccinations and the types of immune cells subsequently infiltrating the glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 49 publications
2
91
0
Order By: Relevance
“…Previous studies (Sokratous, Polyzoidis & Ashkan, 2017) demonstrated that immune cell activation accelerates tumor growth and progression, influencing tumor microenvironments. The key finding in this study indicated a high correlation between EMILIN/Multimerin expression and immune infiltration levels in LGG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Sokratous, Polyzoidis & Ashkan, 2017) demonstrated that immune cell activation accelerates tumor growth and progression, influencing tumor microenvironments. The key finding in this study indicated a high correlation between EMILIN/Multimerin expression and immune infiltration levels in LGG.…”
Section: Discussionmentioning
confidence: 99%
“…Sokratous G et al suggested that the infiltration level of cytotoxic T cell in glioma could importantly affect the clinical prognosis [39]. However, the biological function of these immune cells in glioma has not be fully and comprehensive explored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Sokratous et al 2017) and neutrophils and dendritic cells. Currently, studies illustrate that EMILIN/Multimerins display many functions regulating tumor growth and lymph node metastases.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 92%